Концептуальные основы развития инновационной инфраструктуры в транзитивной экономике - Мухамедова, З.Х. (Культура народов Причерноморья, 2014)
Обоснована важность поддержки инноваций и развития необходимой для них инфраструктуры для транзитивных экономик. Рассмотрена сущность инновационной инфраструктуры, основные ее блоки и виды учреждений (образований). Выделены характерные проблемы транзитивной экономики, а также специфические проблемы, которые блокируют инновации. Определены особенности создания инновационной инфраструктуры в условиях рыночных трансформаций. Предложены концептуальные основы развития такой инфраструктуры, в частности интегрированный и инклюзивный подход, который должен реализовываться на управленческом, системном и практическом уровнях. Обоснована необходимость создания гибридных структур, объединяющих различные функции. Сформулированы рекомендации по расширению роли инновационной инфраструктуры в активизации инноваций. Обґрунтовано важливість підтримки інновацій та розвитку необхідної для них інфраструктури для транзитивних економік. Розглянуто сутність інноваційної інфраструктури, основні її блоки і види установ (утворень). Виділено характерні проблеми транзитивної економіки, а також специфічні проблеми, які блокують інновації. Визначено особливості створення інноваційної інфраструктури в умовах ринкових трансформацій. Запропоновано концептуальні засади розвитку такої інфраструктури, зокрема інтегрований і інклюзивний підхід, який повинен реалізовуватися на управлінському, системному і практичному рівнях. Обґрунтовано необхідність створення гібридних структур, що об'єднують різні функції. Сформульовані рекомендації з розширення ролі інноваційної інфраструктури в активізації інновацій. The study substantiates the importance of supporting innovations and necessity of developing the relating infrastructure for transition economies. The points under consideration are: principles of innovation infrastructure, its basic integral parts and institutional types. Innovation infrastructure which performs a certain number of functions for the implementation of innovative processes is given detailed consideration as the basis for the state system of innovations and know-how market. Were highlighted typical problems of the transitive economy, as well as specific problems that inhibit innovations. Stated peculiarities of creating the innovative infrastructure in the context of market transformations while taking into account specificity of the transitive economy and its practical features. Were suggested conceptual principles of development for such infrastructure, in particular, an integral and inclusive approach which must be implemented at the administrative, system-related and practical levels. Substantiated the necessity of creating hybrid structures that combine different functions. Stated recommendations on enhancing the role of innovation infrastructure in activating innovations.